FOREIGN INVESTMENT OPPORTUNITIES IN IMPROVING THE COUNTRY'S ECONOMY POST COVID-19 PANDEMIC - Marasabessy, Ruslan Husein; Nazaruddin, Nirwan (STAI Asy-Syukriyyah, 2022)
In terms of the economic development of a nation it cannot be separated from economic activities that are stable in a country, on the other hand it is undeniable that now the world is struggling against the Covid-19 pandemic which is known together with all countries is intensively making movements aimed at Minimizing the spread of the corona virus, recorded based on data from the Google news site related to the development of Covid-19 cases throughout the country, the total cases worldwide were recorded at 50,794,593 with cases of patients dying as many as 1,262,199 Various policies were created by the government in order to attract the attention of foreign investors to enter Indonesia to invest, one of which is the open door policy to improve the country's economy after the Covid-19 pandemic in the future.